Effects of structural strain and phase transformations on the mechanical properties of alumina-zirconia-graphene composites - Faglioni, Felipe Dias [UNESP]; Pereira, Cristian Guilherme Barbosa [UNESP]; Foschini, Cesar Renato [UNESP]; Estrada, Flávia Regina (Elsevier, 2024)
Yttria-stabilized-zirconia (YSZ) plus graphene-based-materials composites may present phase transitions. Consequently, it may affect the composite properties. Thus, this work discusses the causality between lattice strain, phase transition, fracture toughness (Kc) and hardness (H) values in alumina+YSZ matrix reinforced with 0 wt.% up to 1.25 wt.% multilayered-graphene (MLG). The conventional sintering was made in a reducing atmosphere. H and Kc were obtained by Vickers indentation. The structural characterization shows that the MLG addition promoted an increase in YSZ lattice parameters and a phase transition, from tetragonal to cubic. As a result, the optimum reinforcement peak in the H and in the Kc happens in different MLG concentrations. The Kc optimum is in lower MLG amount, explained by microstructural features. On the other hand, the optimum H displaced to higher MLG concentration may be effect of increasing lattice parameters and the cubic-YSZ phase proportion.
Keywords: Fracture-toughness; Hardness; Rietveld refinement; Synchrotron XRD; Yttria stabilized zirconia